Eficiencia de Lactobacillus y Chlorella Sp (in vitro), en la disminución de la carga orgánica en aguas residuales de la destilería de alcohol La Soledad, Junín - García Hernández, Jorge Luis (2016)
This investigation was made in the community La Soledad of the canton Junín with the objective to verify the efficiency of Chlorella sp and Lactobacillus, in the decrease of organic load of the waste water of the alcohol distillery of "La Soledad", for these samples were taken from the lagoon of the distillery to make the characterization of the residual water, the analyses made were: nitrites that had 10 mg/dm3, phosphate had 470 mg/dm3, solid total had 17813 mg/dm3, DBO had 10000 mg/dm3, dissolved oxygen with 0,82 mg/dm3, pH had 3,81, the temperature was of 33°C, a DCA was in use, 6 treatments were made: T1 = Lactobacillus with application dose of 0,30 ml/dm3; T2 = Lactobacillus with application dose of 0,45 ml/dm3; T3 = Lactobacillus with application dose of 0,60 ml/dm3; T4 = Chlorella with application dose of 0,30 ml/dm3; T5 = Chlorella with application dose of 0,45 ml/dm3 and T6 = Chlorella with application dose of 0,60 ml/dm3, a follow-up was made with analysis and capture of information every 10 days by 30 days, to observe the behavior of the sample of residual water with the inoculated microorganisms, then the efficiency of the microorganisms was evaluated with regard to the reduction of the organic load, being the most efficient the T1 Lactobacillus with a final DBO of 1500 mg/dm3 and an efficiency of 85 %, coming to the conclusion that T1 is the best of the treatments.